Diagnostic Yield and Immediate Complications of Ultrasound guided Interventional Procedures in Bronchogenic Carcinoma in Multidetector Computed Tomography - Paudel, Sharma; Bhusal , Kabi Raj; Kayastha, Prakash; Suwal, Sundar; Katwal, Shailendra; Thapa, Madan (Nepal Journal of Medical Sciences, 2024)
Introduction: Lung cancer is the second most common cancer and most common cause of cancer mortality worldwide. Ultrasound is helpful in evaluation and to perform biopsy from lung mass, enlarged lymph nodes and from accessible metastatic lesion. It also aids to perform thoracocentesis. The purpose of this study was to assess the diagnostic yield of the interventional procedures under sonographic guidance in suspected bronchogenic carcinoma and to look for immediate complications of the procedures. Methods: A prospective analytical study was conducted in the Department of Radiology and Imaging, Tribhuvan University Teaching Hospital (TUTH) in 46 patients (48 procedures) with Contrast Enhanced Computed Tomography (CECT) diagnosis of bronchogenic carcinoma from June 2022 to August 2023.Ethical clearance was obtained from Institutional Review Committee of Institute of Medicine (Reference No. 56 (6-11) E2 079/80). Ultrasound guided biopsy from lung mass, lymph nodes and metastatic liver lesion was performed. Thoracocentesis was performed in patients with pleural effusion. Immediate complications were recorded. Histopathology/cytology reports were collected, and diagnostic yield was calculated by binary classification. Results: The overall diagnostic yield was 89.58% (43 out of 48 procedures). The highest yield was obtained from biopsy done from metastatic liver lesion and was 100% (n=1). Diagnostic yield from biopsy of lung mass was 93.93% (n=33) and that from supraclavicular lymph node was 87.50% (n=8). Diagnostic yield from pleural fluid cytology was 66.67% (n=6). Minor complications occurred in 18.75% (n = 9) of patients. Approximately 14.58% (n = 7) patients complained of pain. Only one required injectable pain killer for management. Small pneumothorax occurred in 4.17% (n=2) of cases which resolved with high flow oxygen supply. Conclusions: In patients with contrast enhanced computed tomography diagnosis of bronchogenic carcinoma, ultrasound guided diagnostic procedures have good efficacy and safety. Ultrasound should be routinely used for the diagnosis of lung cancer when feasible.